Reasons for nonuse of contraceptive methods by women with demand for contraception not satisfied: an assessment of low and middle-income countries using demographic and health surveys - Laísa Rodrigues Moreira; Fernanda Ewerling; Aluisio J. D. Barros; Mariangela Freitas Silveira (BMC, 2019)
Abstract Background Nonuse of contraceptive methods by women in need of contraception may impact their sexual and reproductive health. The aim of this study was to describe the reasons for nonuse of contraception among women with demand for contraception not satisfied in low and middle-income countries (considering both overall countries and various subgroups of women). Methods We used the latest Demographic and Health Survey data from 47 countries. A descriptive analysis of the reasons for nonuse of contraceptive methods was performed among sexually active women with demand for contraception not satisfied. The prevalence of each reported reason was also evaluated according to marital status, woman's age and schooling, area of residence, wealth index, and parity. Wealth-related absolute inequality for each reason was also evaluated using the Slope Index of Inequality. A pro-rich inequality pattern means that the reason is more prevalent among the richest women while a pro-poor means the reason is more common among the poorest ones. Results On average, 40.9% of women in need of contraception were not using any contraceptive methods to avoid pregnancy. Overall, the most prevalent reasons for nonuse of contraceptives were "health concerns" and "infrequent sex," but the prevalence of each reason varied substantially across countries. Nonuse due to "opposition from others" was higher among married than unmarried women; in turn, the prevalence of nonuse due to "lack of access" or "lack of knowledge" was about two times higher in rural areas than in urban areas. Women with less schooling more often reported nonuse due to "lack of access." Pro-rich inequality was detected for reasons "health concerns," "infrequent sex," and "method-related", while the reasons "other opposed," "fatalistic," "lack of access," and "lack of knowledge" were linked to patterns of pro-poor inequality. Conclusions Family planning promotion policies must take into account the different reasons for the nonuse of contraceptive methods identified in each country as well as the contextual differences regarding women of reproductive age (such as social norms and barriers that prevent women from accessing and using contraceptives).